2018
DOI: 10.3390/ma11040579
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Thermo-Responsive Methylcellulose Hydrogels for Cell-Sheet Engineering

Abstract: A possible strategy in regenerative medicine is cell-sheet engineering (CSE), i.e., developing smart cell culture surfaces from which to obtain intact cell sheets (CS). The main goal of this study was to develop 3D printing via extrusion-based bioprinting of methylcellulose (MC)-based hydrogels. Hydrogels were prepared by mixing MC powder in saline solutions (Na2SO4 and PBS). MC-based hydrogels were analyzed to investigate the rheological behavior and thus optimize the printing process parameters. Cells were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 36 publications
1
57
0
Order By: Relevance
“…Due to this reason, commercially available mc usually is characterized by its viscosity (of a 2% solution at 20°C) and the molecular weight is a recalculated value, which does not allow drawing conclusions for the distribution of the molecular weight. We found that most studies [32][33][34][35][36][37][38][39][40][41] used an mc with a given viscosity of 4000 mPa s (M n ≈ 86 kDa); 30 these studies have in common to have achieved printing of multiple layers and only limited collapse of predesigned macropores. Other studies 42,43 reported about the use of mc with a given viscosity of 15 mPa s (M n ≈ 14 kDa) and found significant improvements of the printed shape fidelity in presence of mc compared to mc-free controls, but those structures lacked the evidence of multiple layer stacking.…”
Section: Biomaterials Science Minireviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to this reason, commercially available mc usually is characterized by its viscosity (of a 2% solution at 20°C) and the molecular weight is a recalculated value, which does not allow drawing conclusions for the distribution of the molecular weight. We found that most studies [32][33][34][35][36][37][38][39][40][41] used an mc with a given viscosity of 4000 mPa s (M n ≈ 86 kDa); 30 these studies have in common to have achieved printing of multiple layers and only limited collapse of predesigned macropores. Other studies 42,43 reported about the use of mc with a given viscosity of 15 mPa s (M n ≈ 14 kDa) and found significant improvements of the printed shape fidelity in presence of mc compared to mc-free controls, but those structures lacked the evidence of multiple layer stacking.…”
Section: Biomaterials Science Minireviewmentioning
confidence: 99%
“…21 Thus, the stability of printed mc-containing constructs, as well as their degradation behaviour can be controlled by the presence of salts in the (bio-)ink and the cell culture medium. The best printing results of salt-doped mc-inks were achieved by printing in the range of 20-25°C, 39,40 which created the optimum for viscous behaviour of mc in sol form near to the gelation state.…”
Section: Biomaterials Science Minireviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, it is understood that some diseases induce changes in body temperature; thus, thermoresponsive polymers may be a useful tool for diagnostic purposes. 50 With regard to thermoresponsive hydrogels, Cochis et al 52 used methylcellulose for cellsheet engineering. After optimising the printing process parameters, methylcellulose hydrogel rings were extruded for the first time.…”
Section: Four-dimensionalmentioning
confidence: 99%